The Influence of Principal's Transformational Leadership and Organizational Culture on Junior High School Teacher Performance in Paal Dua District, Manado City - Armando Vikri Kalalo; Harol R. Lumapow; Elni J. Usoh; Romi J. Mongdong (JR Education, 2026)
Teacher performance is a critical determinant of educational quality and plays a central role in achieving national educational goals, yet it remains suboptimal in many school settings due to weak leadership and organizational dynamics. This study aims to empirically analyze the influence of the principal's transformational leadership and organizational culture—both partially and simultaneously—on junior high school teacher performance in Paal Dua District, Manado City. A quantitative approach with an associative ex-post facto method was employed, with data collected from 85 teachers selected via proportionate stratified random sampling from a population of 108 using the Slovin formula; data were gathered through Likert-scale questionnaires tested for validity and reliability. The multiple linear regression analysis yielded the equation Y = −0.317 + 0.495X1 + 0.432X2. Transformational leadership had a significant positive partial effect on teacher performance (t = 8.794, Sig. = 0.001 < 0.05), as did organizational culture (t = 6.853, Sig. < 0.001). Simultaneously, both variables produced a significant combined effect (F = 61.679, Sig. = 0.001 < 0.05), with a coefficient of determination (R²) of 0.601, indicating that 60.1% of variation in teacher performance is explained by the two predictors. It is concluded that the synergy between an inspiring principal and a conducive organizational culture is the primary determinant in optimizing teacher professionalism. These findings imply that educational policymakers should integrate transformational leadership development with organizational culture strengthening as a unified strategy for improving teacher performance in Indonesian junior high schools.